Evaluating the impact of hexagon fraud on potential financial statement fraud with audit quality as a moderator - Winata, Liana Angelina; Suhartono, Sugi; Dema, Yosef (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Agency theory states that fraudulent financial reporting involves deliberate actions that misrepresent financial data, often driven by conflicting interests between agents and principals. On the other hand, the GONE theory attributes fraud to greed, opportunity, needs, and exposure. This study investigates the influence of the fraud hexagon on the likelihood of fraudulent financial reporting, with audit quality as a moderating factor. Therefore, the authors purposively selected 40 industrial sector companies listed on the Indonesian Stock Exchange from 2020 to 2022, ending with 120 observations as the sample. Data analysis with pooling tests and MRA tests reveals that total asset accrual and holding multiple positions contribute to the potential for fraudulent financial reporting. However, financial targets, CEO education, engagement in government projects, and industry nature exhibit no significant impact. Additionally, the moderating effect of audit quality fails to mitigate the positive influence of financial targets and industry nature on fraudulent financial reporting potential. Future research can employ logistic regression and incorporate additional independent variables.